Deformation behaviour and strain rate sensitivity of 304L SS at elevated temperatures. (3rd September 2022) - Singh, Balbir Kumar; Christopher, J.; Selvi, Panneer; Mishra, Jagannath; Reddy, G.V. Prasad
ABSTRACT: Tensile deformation behaviour of nuclear grade 304 L SS (PHWR calandria vessel material) was presented at temperatures 300 K to 1123 K and at three different strain rates. The deformation behaviour is influenced by the strain-induced martensitic transformation at 300 K, the occurrence of dynamic strain ageing (DSA) at intermediate temperatures (573–873 K) and the dominance of strain softening at high temperatures (973–1123 K). The occurrence of DSA caused anomalies in flow behaviour and ductility for the steel. At high temperatures, strain softening manifested in a rapid decrease in flow strength with increasing temperature and decreasing strain rate. Further, instantaneous (mi ) and quasi-steady state strain rate sensitivity (ms ) with strain were evaluated using strain rate jump tests. At low and DSA temperatures, the initial and quasi-steady transient response differs. Contrary to this, the value of mi is equal to ms at high temperatures.